Cutaneous Larva Migrans On The Hand - Fadlul Azim Fauzi Mansur; Tiew Kee Hup; Jerzy M. Behnke (USIM Press, 2024)
Vol. 7 No. 3 (2021): Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience (Case Report)